2022
DOI: 10.1111/ajag.13114
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Without Age: An Australian residential aged care home experience

Abstract: Objective: Cycling Without Age (CWA) involves taking residents on outdoor trishaw (electric bicycle) rides driven by trained 'pilots'. This study explored the CWA experience from the perspective of residents and family members, staff and volunteer pilots from a residential aged care home in Queensland, Australia.Methods: A qualitative descriptive design was used. Interviews were conducted with 21 participants. Transcripts were analysed thematically, with the interview questions determining a priori categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Overall, the themes identified in this study align with findings from similar studies. Cyarto et al [ 22 ] found that CWA was associated with experiencing reminisced positive emotions and gave meaningful experiences. Gray et al [ 20 ] found that the core of CWA was meeting new people and engaging in a shared experience, and McNiel and Westphal [ 21 ] found that participating in CWA gave nursing home residents the possibility of fresh air and social connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the themes identified in this study align with findings from similar studies. Cyarto et al [ 22 ] found that CWA was associated with experiencing reminisced positive emotions and gave meaningful experiences. Gray et al [ 20 ] found that the core of CWA was meeting new people and engaging in a shared experience, and McNiel and Westphal [ 21 ] found that participating in CWA gave nursing home residents the possibility of fresh air and social connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggest that participating in CWA rides has positive short-term effects on the participants’ mood and wellbeing [ 19 ] and is associated with of positive emotions [ 20 ]. Moreover, participation in the bike rides facilitate socialization among residents [ 21 ] and provide an opportunity for them to spend time outside the nursing homes, rediscovering familiar places within the community [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…weather conditions, length and duration of rides, mood of the pilots prior to the rides, and environment). The programme's effect on quality of life and immediate impact on happiness have been mentioned, anecdotally, numerous times by programme founder, Ole Kassow [15], and qualitatively by McNiel and Westphal, Cyarto et al, and Christensen [9,10,12], who argued that "breaths of fresh air" and "break from daily routines" were prominent feelings among "Cycling Without Age" passengers. The trishaw rides allowed them to enjoy "the natural environment away from the home" [12], promoting relationships, togetherness and joy [10], all hypothesized to contribute to positive emotions, and thus positively impact life satisfaction, mood and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The programme's effect on quality of life and immediate impact on happiness have been mentioned, anecdotally, numerous times by programme founder, Ole Kassow [15], and qualitatively by McNiel and Westphal, Cyarto et al, and Christensen [9,10,12], who argued that "breaths of fresh air" and "break from daily routines" were prominent feelings among "Cycling Without Age" passengers. The trishaw rides allowed them to enjoy "the natural environment away from the home" [12], promoting relationships, togetherness and joy [10], all hypothesized to contribute to positive emotions, and thus positively impact life satisfaction, mood and well-being. Cyarto et al further hypothesized that mood improvements might be caused by visits to destinations of relevance to the passengers' pasts and storytelling during rides, both prominent elements in reminiscing (which is an effective intervention for life satisfaction among nursing home residents [38]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation